2019
DOI: 10.1016/j.cmi.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and culture of Methanobrevibacter smithii by co-culture with hydrogen-producing bacteria on agar plates

Abstract: Objectives: Methanogenic Archaea are considered as extremely oxygen-sensitive organisms, and their culture is fastidious, requiring specific equipment. We report here conditions allowing the cultivation of Methanobrevibacter smithii in an anaerobic chamber without the addition of hydrogen. Methods: We first enriched the stool sample in an anaerobic liquid medium. To cultivate M. smithii with Bacteroides thetaiotaomicron and other hydrogen-producing bacteria on solid medium in an anaerobic chamber, we divided t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Such cross-feeding likely explains why the relative abundances of M. smithii and fermenting bacteria are often positively correlated (21,23,24). Several studies have shown that in the laboratory, M. smithii can grow from the H 2 provided by Bacteroides thetaiotaomicron, a common gut commensal bacterium (25)(26)(27). Given that the cultured representatives of the Christensenellaceae ferment simple sugars (16,28) and that their genomes contain hydrogenases (29), we predicted that members of the Christensenellaceae produce H 2 used by M. smithii as a substrate in methanogenesis.…”
mentioning
confidence: 99%
“…Such cross-feeding likely explains why the relative abundances of M. smithii and fermenting bacteria are often positively correlated (21,23,24). Several studies have shown that in the laboratory, M. smithii can grow from the H 2 provided by Bacteroides thetaiotaomicron, a common gut commensal bacterium (25)(26)(27). Given that the cultured representatives of the Christensenellaceae ferment simple sugars (16,28) and that their genomes contain hydrogenases (29), we predicted that members of the Christensenellaceae produce H 2 used by M. smithii as a substrate in methanogenesis.…”
mentioning
confidence: 99%
“…3g-j) but does not aggregate in mono-culture before 7-10 days of culture (data not shown). In contrast, B. thetaiotaomicron, used here as a positive control based on previous reports that it supports the growth of M. smithii via H 2 production (25, 26), did not flocculate when grown alone, (Fig. 2c) and, when co-cultured with M .…”
Section: Resultsmentioning
confidence: 99%
“…thetaiotaomicron has previously been shown to support the growth of M . smithii in co-culture (25, 26). B .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogenotrophic methanogens of Methanospirillum sp., Methanobrevibacter sp., and Methanoculleus sp. [40][41][42] and aceticlastic methanogen of Methanothrix sp. [43] were predominant archaea in 35 ‱ C anaerobic sludge.…”
Section: Microbial Communitymentioning
confidence: 99%